LENIENCY POLICY IN EUROPEAN CARTEL ENFORCEMENT - Oppermann (Leibniz University of Hannover), Bernd (Duc In Altum - Cadernos de Direito, 2016)
Leniency programs stand for a rather easy collection of evidence and intel-ligence. Added value is achieved by hindering upcoming and maintain-ing cartels to develop an organiza-tional structure. Leniency also in-creases uncertainty on the side of the cartel members and makes it more difficult for cartel participants to reach an agreement. Furthermore, the costs of adjudicating are decreased by the legal goal-oriented activity of whistle blowers. Therefore, the leniency programs of the EU and of the most member states proved to be a success story on the one hand. In contrary, there are a few adverse effects. In a theoretical approach, the notion of leniency is contradictory since blowing the whistle is the second best choice only. To make the exemption to become the rule gives wrong incentives to the market members to opt for the first best choice in order to build a cartel either not punished or not discovered and keep silent. For quite some principle reasoning such view would create an obstacle. Moreover practically, some adverse effects have been discussed. For my part, the most crucial notion is that leniency programs are thought to help to find out well hidden cartels, in other words to encourage discovery in hard cases. Instead, leniency is not eligible to be the main tool of lazy cartel enforcement. For regular investigation, there are other incentives in the law of discovery, in procedural law, and last but not least in private enforcement due to the action provided by the legal order of member states. However, I would not hesitate to vote for its limited supplementary use in cartel matters.